2004
DOI: 10.1517/14656566.5.12.2615
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ivermectin and thiabendazole in the treatment of strongyloidiasis

Abstract: Treatment of strongyloidiasis has been traditionally based on thiabendazole, despite its frequent gastrointestinal side effects and failure to achieve eradication of the parasite from faeces in approximately 30% of cases. Ivermectin has been shown to be more effective for treating chronic uncomplicated strongyloidiasis. The efficacy and tolerability of these drugs in a series of patients treated from 1999 to 2002 at the Oliva Health Centre, Valencia, Spain, are reported. A total of 88 patients diagnosed of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(52 citation statements)
references
References 14 publications
(13 reference statements)
0
46
0
4
Order By: Relevance
“…This outcome was unexpected as the drug of choice against S. stercoralis is the ivermectin whose cure rates reach 100% as referred by different studies. 4,27,28 Nevertheless, some authors reported values as low as 67%. 29 Uncomplicated infection may be treated with ivermectin 200 μg/kg of body weight single dose, although some reports suggested that two doses of ivermectin on consecutive days provided the best results with regard to efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This outcome was unexpected as the drug of choice against S. stercoralis is the ivermectin whose cure rates reach 100% as referred by different studies. 4,27,28 Nevertheless, some authors reported values as low as 67%. 29 Uncomplicated infection may be treated with ivermectin 200 μg/kg of body weight single dose, although some reports suggested that two doses of ivermectin on consecutive days provided the best results with regard to efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…29 Uncomplicated infection may be treated with ivermectin 200 μg/kg of body weight single dose, although some reports suggested that two doses of ivermectin on consecutive days provided the best results with regard to efficacy. 4,19,27,28 However, to certainly evaluate the results of treatment of S. stercoralis , stool examinations should be performed for at least 1 or 2 years when possible. 27 Even when cure cannot be assured, parasite burden drastically decreased below the threshold of detection after the parasiticide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Single dose of Ivermectin (200 microgram per kilogram of bodyweight) orally was also shown to have superior cure rate of 97% vs 63% with high dose Albendazole 800mg orally daily for seven days [41] . Currently, oral Ivermectin in the dose of 200 microgram per kilogram of bodyweight repeated on two consecutive days or after 2 wk is the preferred drug for treatment of Strongyloides stercoralis (Table 4) [48,49] . In patients who cannot tolerate it orally, alternate routes like subcutaneous administration of Ivermectin has been advised [50] .…”
Section: Sensitivity and Specificity Remarksmentioning
confidence: 99%
“…Because even one remaining adult female can multiply and cause disseminated disease, the goal of treatment is complete eradication of the parasite. The current treatment of choice for chronic strongyloidiasis is single-dose ivermectin (Table 2), although some studies have suggested that two doses of ivermectin, 200 μg/kg, given on consecutive days may have greater efficacy [41]. Ivermectin has better tolerability compared with thiabendazole [42].…”
Section: Treatmentmentioning
confidence: 99%